2020
DOI: 10.3348/kjr.2019.0268
|View full text |Cite
|
Sign up to set email alerts
|

Performance of F-18 Fluorocholine PET/CT for Detection of Hyperfunctioning Parathyroid Tissue in Patients with Elevated Parathyroid Hormone Levels and Negative or Discrepant Results in conventional Imaging

Abstract: Objective: Our aim was to assess the diagnostic performance of F-18 fluorocholine (FCH) positron emission tomography/ computed tomography (PET/CT) in detecting hyperfunctioning parathyroid tissue (HPT) in patients with elevated parathyroid hormone levels with negative or inconclusive conventional imaging results and to compare the findings with those obtained using technetium-99m sestamibi (MIBI) scintigraphy and neck ultrasonography (US). Materials and Methods: Images of 105 patients with hyperparathyroidism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…In the two studies performed by the same group, a heterogeneous population of patients suffering from both primary and secondary HPT was considered, reaching a lesion-based sensitivity of 89% but a detection rate on a per patient level of 92% [17]. More recently, Uslu-Beşli et al confirmed the superiority of choline PET when compared with inconclusive traditional imaging methods [41]. Michaud et al were one of the first to investigate the role of [ 18 F]FCH PET/CT in HPT as second line imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In the two studies performed by the same group, a heterogeneous population of patients suffering from both primary and secondary HPT was considered, reaching a lesion-based sensitivity of 89% but a detection rate on a per patient level of 92% [17]. More recently, Uslu-Beşli et al confirmed the superiority of choline PET when compared with inconclusive traditional imaging methods [41]. Michaud et al were one of the first to investigate the role of [ 18 F]FCH PET/CT in HPT as second line imaging.…”
Section: Discussionmentioning
confidence: 99%
“…FCH PET/CT has been increasingly gaining acceptance as the best imaging modality [ 15 25 ]. Compared to conventional functional imaging, FCH-PET/CT does not only have superior sensitivity, but also better spatial resolution, lower radiation exposure, and shorter study time [ 15 , 20 , 21 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…A recent systematic review (23 articles, 1112 patients) compared FCH-PET/CT with conventional morphological and functional imaging in patients with biochemical hyperparathyroidism and found that FCH-PET/CT sensitivity ranged from 58 %-100 % which may be related to type of conventional imaging, patient population, and FCH-PET/CT protocol [ 18 ]. More recent studies found FCH-PET/CT sensitivity of 91 % (84/92 lesions) when defining lesions with both positive and inconclusive FCH uptakes as positive [ 19 ], 94 % in 101 patients with PTH-dependent hypercalcemia and negative or discordant conventional imaging (vs. 45 % and 44 % for MIBI scan and US, respectively) [ 20 ], 92 % in 103 patients (vs. 39–56 % for conventional scintigraphy) [ 21 ], and 62 % 47 patients after inconclusive first line imaging including US and subtraction scan [ 22 ]. Previous meta-analyses showed pooled sensitivity of 90 % (8 studies, 272 patients) [ 15 ] and of 95 % on per-patient analysis and 92 % on per-lesion analysis ( 14 studies, 517 patients) [ 16 ].…”
Section: Case Presentationmentioning
confidence: 99%
See 2 more Smart Citations